Endoscopic Findings and Histopathological Patterns of Gastric Mucosal Biopsies in Functional Dyspepsia: A Clinicopathological Study - Mohammad Mahdi Hayatbakhsh Abbasi; Elham Jafari; Mohamad Javad Zahedi; Sodaif Darvish Moghaddam; Reza Malekpoor Afshar; Mahdieh Saeedi; Sahar Pooyan Far (Journal of Kerman University of Medical Sciences, 2023)
Background: Endoscopic examination of the gastrointestinal tract through macroscopic and histopathological evaluation provides a tool to differentiate the major causes of functional dyspepsia. The distinction is not always clear. This study aimed to assess the frequency and type of the macroscopic and histopathological changes in gastrointestinal tract endoscopy in patients with symptoms of functional dyspepsia. Methods: A cross-sectional study was performed on 97 patients aged 10–85 years who underwent gastroscopy due to functional dyspepsia symptoms. The patients had no history of weight loss, major comorbidities like diabetes or cirrhosis, non-steroidal anti- inflammatory drug (NSAID) consumption, peptic ulcer, or any other confounding causes. Biopsy specimens were taken from the stomach and duodenum for histopathological examination. The presence of Helicobacter pylori infection was established based on histopathological examination and a positive rapid urease test. Results: Gastric biopsies of 97 patients with functional dyspepsia were studied. In histological examination of gastric mucosal biopsies, chronic inflammation was present in 94 (96.9%), activity was seen in 47 (48.5%), glandular atrophy was seen in 3 (3.1%), and intestinal metaplasia was seen in 9 (9.2%) patients. H. pylori was identified on gastric mucosal biopsies in 46 (47.4%) patients based on sections stained with H&E and Giemsa. Conclusion: According to the obtained results, it is concluded that patients with functional dyspepsia have a higher frequency of gastric mucosal inflammation and H. pylori infection.